ANALISIS PENGARUH TINGKAT PENDIDIKAN, INVESTASI DAN UPAH MINIMUM TERHADAP KESEMPATAN KERJA DAN PERTUMBUHAN EKONOMI - Kusuma Wati, Ni Wayan Aprilia; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 4 (2023): Vol.12.4.APRIL.2023[231-310]DO - 10.24843/EEP.2023.v12.i04.p05, 2023)
Various efforts are made by the government to increase economic growth for the region itself and are expected to get positive results for job opportunities in the Regency / city of Bali Province. The purpose of the study is to analyze the level of education, investment and minimum wage on employment opportunities and economic growth in the Regency / City of Bali Province. The data collection method is carried out through data published by BPS Bali Province. The analysis technique used is path analysis. The selected panel data regression analysis techniques are fixed effect model and common effect model using Eviews software. The results of this study: 1) The level of education has a positive and insignificant effect on employment opportunities while investment and minimum wages have a positive and significant effect on employment opportunities. 2) The level of education and investment has a negative and insignificant effect on economic growth while the minimum wage has a negative but significant effect and employment opportunities have a positive and significant effect on economic growth. 3) The level of education, investment and minimum wage have an indirect effect on economic growth through employment opportunities in the Regency / City of Bali Province. keyword : education, investment, minimum wage, employment opportunities, economic growth